Chronic Kidney Disease After Liver Transplantation: Impact of Extended Criteria Grafts. Issue 6 (21st May 2019) - Kalisvaart, Marit; Schlegel, Andrea; Trivedi, Palak J.; Roberts, Keith; Mirza, Darius F.; Perera, Thamara; Isaac, John I.; Ferguson, James; de Jonge, Jeroen; Muiesan, Paolo
Abstract : The use of extended criteria donor (ECD) grafts has been associated with acute kidney injury (AKI) after liver transplantation. However, the relation between graft quality and development of chronic kidney disease (CKD) remains unknown. Therefore, the aim of this study was to analyze the impact of ECD grafts for CKD after liver transplantation. All patients (2007‐2015) transplanted for end‐stage liver disease at our center were assessed. Longterm kidney function was divided into 4 groups: no CKD (estimated glomerular filtration rate [eGFR], ≥60 mL/minute/1.73 m 2 ), mild CKD (eGFR, 30‐59 mL/minute/1.73 m 2 ), severe CKD (eGFR, 15‐29 mL/minute/1.73 m 2 ), and end‐stage renal disease (ESRD). Marginal donation after brain death (DBD) grafts (donor age, >70 years; body mass index, >35 kg/m 2 ; cold storage, >12 hours) and donation after circulatory death (DCD) grafts were considered ECD grafts. Overall, 926 patients were included, and 43% received an ECD graft (15% marginal DBD; 28% DCD). After 5 years, 35% developed CKD; severe CKD and ESRD occurred in only 2% and 1%, respectively. CKD rates were comparable for all 3 graft groups (standard group, 36%; marginal DBD group, 29%; DCD group, 35%; standard versus marginal DBD groups, P = 0.16; standard versus DCD group, P = 0.80). None of the ECD criteria were identified as independent risk factors in a Cox regression model for CKD. Risk factors included recipient age, female sex, and preoperative kidney function. Furthermore, recipients who had severe acute kidney injury (AKI; Kidney Disease: Improving Global Outcomes stages 2 and 3) had a 1.8‐fold increased risk for CKD. Longterm kidney function of recipients with severe AKI depended on the recovery of kidney function in the first postoperative week. In conclusion, there is no direct relation between the use of ECD grafts and CKD after liver transplantation. However, caution should be taken in recipients who experience severe AKI, regardless of graft type.